Pengaruh Penggunaan Digital Banking dan Minat Investasi terhadap Pertumbuhan Ekonomi di Jawa Barat - Avwa, Pina Ainul; Vidiati, Cory; Selasi, Dini; Pratama, Gama (JIOSE: Journal of Indonesian Sharia Economics, 2024)
The advancement of digital technology is experiencing rapid development at any time. The development of increasingly sophisticated technology has an impact on the development of all business sectors, one of which is digital banks. The purpose of this study is to conduct an in-depth investigation of the use and interest in investment in digital banks in the community in West Java. The method used in this study is a quantitative method. The results of the study show that the use of digital banks is more in demand while investment is still less popular because more transactions use online methods. This study concludes that the use of digital banks and investment interest have a simultaneous effect on economic growth.